The Effect of Tax Extensification on Income Tax Revenue : Study on One KPP In Bandung City - Agistina Suryani; Siti Mialasmaya; Djajun Juhara; R. Deni Purana (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
This research is to determine the effect of tax extensification on income tax receipts at one of the Tax Offices in Bandung. This research method uses quantitative research methods with descriptive and verification approaches. First, obtain the questionnaire results from the respondents, then process them through SPSS 20 to be tested, and then present the output results. After conducting analysis and discussion, the authors conclude that tax extensification positively influences income tax receipts at one of the tax offices in the city of Bandung. Therefore, to increase the magnitude of the effect of Tax Extensification on Income Tax Revenue, one of the Tax Offices in the City of Bandung should carry out Extensification activities consistently to be able to continue to increase the number of Taxpayers, establish cooperation with related external parties to improve the Tax Extensification strategy, such as employment agencies/treasurers government. The government agency in question is the Regional Government. In order to find out the number of Taxpayers and to know more about Taxpayers, as well as cooperate with the private sector, namely cooperation with employers in companies registered at the Bandung Cibeunying Primary Tax Service Office to make it easier for their employees who have not registered in enroll en masse.